Tommy [compact disc] - Entwistle, John, 1944-2002; Daltrey, Roger; Townshend, Pete; Moon, Keith, 1946-1978 (MCA, 1996)
The classic rock opera features epic tracks such as I'm Free; Pinball Wizard; Sensation; Christmas; We're Not Gonna Take It; and the dramatic ten-minute instrumental Underture.